The minimalist lifestyle as resistance in the era of global consumerism: A case study of the Lyfe With Less community - Qurrota A'yun; Amal Taufiq (Jurnal Sosiologi Dialektika, 2026)
Consumption activities in the global era are no longer carried out to meet basic needs and become a place to display identity and social status. Jean Baudrillard refers to the phenomenon as a consumerist society where consumption activities are carried out based on the symbolic value inherent in a product or goods. This article examines the practice of a minimalist lifestyle as a form of resistance to consumer culture through a study of the Lyfe With Less community. This study uses a qualitative method, specifically netnography. Data were collected through netnographic observations, interviews, and documentation. The results of the study show that minimalist living practices carried out by members of the Lyfe with Less community, such as decluttering, using goods to the end, being wise in consumption, and choosing environmentally friendly products, reflect a conscious effort to escape the logic of excessive consumption. This study concludes that although the minimalist lifestyle can be trapped in a system of new signs and symbolic commodifications, this community suggests that minimalism restores the meaning of consumption as a functional and responsible act and can be a strategy of meaningful living that rejects the values of consumerism.